Identification of simvastatin-regulated targets associated with JNK activation in DU145 human prostate cancer cell death signaling - Jung, Eun Joo; Chung, Ky Hyun; Kim, Choong Won (BMB reports, 2017)
The results of this study show that c-Jun N-terminal kinase (JNK) activation was associated with the enhancement of docetaxel-induced cytotoxicity by simvastatin in DU145 human prostate cancer cells. To better understand the basic molecular mechanisms, we investigated simvastatin-regulated targets during simvastatin-induced cell death in DU145 cells using two-dimensional (2D) proteomic analysis. Thus, vimentin, Ras-related protein Rab-1B (RAB1B), cytoplasmic hydroxymethylglutaryl-CoA synthase (cHMGCS), thioredoxin domain-containing protein 5 (TXNDC5), heterogeneous nuclear ribonucleoprotein K (hnRNP K), N-myc downstream-regulated gene 1 (NDRG1), and isopentenyl-diphosphate Delta-isomerase 1 (IDI1) protein spots were identified as simvastatin-regulated targets involved in DU145 cell death signaling pathways. Moreover, the JNK inhibitor SP600125 significantly inhibited the upregulation of NDRG1 and IDI protein levels by combination treatment of docetaxel and simvastatin. These results suggest that NDRG1 and IDI could at least play an important role in DU145 cell death signaling as simvastatinregulated targets associated with JNK activation. [BMB Reports 2017; 50(9): 466-471].